Evaluating Morphology of the Peritalar Joints Using Surface Mapping Based 3D Remodeling Technique: A Large Sample Sized Cadaveric Study - Conor Wallace BS; Mingjie Zhu DAOM, MPH; Michael Nocek BA; Jingdian Huang BA; Charles Nolte BS; Stephen Wittels MD; Catherine Alder BS; Ariyani Challapalli BS; Todd Baldini MS; Caley M. Orr PhD; Mark Myerson MD; Shuyuan Li MD, PhD (Foot & Ankle Orthopaedics)
Category: Hindfoot; Ankle Introduction/Purpose: Recent studies have highlighted the important role of peritalar joint congruence in maintaining the alignment of the hindfoot. Peritalar subluxation is associated with a variety of pathological deformities including flatfoot, cavovarus foot, clubfoot, as well as foot and ankle stress fractures. To date, studies of peritalar joint congruence have all been performed using either XR, WBCT based direct measurements, or 3D segmentation and analysis. However, none of these techniques can demonstrate the cartilage location nor disruption, nor the exact location of the articulation on the bone surface. Data bias caused by the limitations of these study methodologies is therefore inevitable. This study used 3D surface mapping to assess morphometrics of the cartilage surfaces of the peritalar joints. Methods: 18 fresh-frozen cadaveric feet without trauma nor surgery or significant deformities were dissected to expose the calcaneus, cuboid, talus, navicular bones, and their articular surfaces. Surface mapping of the articular surfaces and bones was completed using an Artec Spider 3D Scanner. Further digital analysis was completed using GeoMagic Studio 10 and Materialise Mimics 22. Descriptive and comparative analyses were performed using SAS software. Paired T-test was used to compare the size of articular surfaces in each joint. Statistical significance level was set to P < .05. Results: Detailed information of the articular surfaces is summarized in Table 1. The average articular area on both sides of the joint matched each other well in the posterior facets of the subtalar joint (5% difference), and calcaneocuboid joint (6% difference) without significant statistical difference, but not in the anterior & middle facets of the subtalar joint, nor the talonavicular joint. In the anterior & middle facets of the subtalar joint, the cartilage articular area on the talus side was 121% of that on the calcaneus mostly due to the difference between middle facet (p < 0.05); and in the talonavicular joint the cartilage articular area on the navicular was 144% of that on the talus (p < 0.05). Conclusion: The cartilage articular surfaces in certain peritalar joints do not match its opposing surface in size. In the talonavicular joint, it is easy to understand since area of the socket must be much smaller than that of the ball in order for the joint to glide and rotate. There must be functional reasons for this phenomenon to happen in the anterior and middle facets of the subtalar joint, which need further investigation. This study shows that the extent of subluxation of the peritalar joints may be physiological and should not necessarily be considered as pathological.